THE ROLE OF MISINVOICING IN THE MONEY LAUNDERING CYCLE - Iyanda, Adebayo E (Journal of Anti-Corruption Law, 2023)
Traditionally, the emphasis of trade-based money laundering policy development has been directed towards financial transactions where the origin of capital is illegal, neglecting private sector companies utilising trade to launder money. Thus, can commercial businesses which engage in trade misinvoicing through crossborder trade be prosecuted for money laundering? With limited understanding of the money laundering cycle in international trade, it will be difficult for prosecutors to bring money laundering charges against commercial businesses operating in this sector.